Implementasi Six Sigma Untuk Mengurangi Defect Produk Hijab Print Dengan Metode DMAIC - Rohmadi, Agus Bekti; Junaedi, Didi (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
Due to the large amount of muslims in Indonesia, there is a high demand for islamic clothing. However, the high competition in this sector encourages customers to get high quality products at lower prices. As a result, manufacturers need to implement quality control as part of an integrated continuous development process to reduce the proportion of defects and increase productivity. In a case study, the number of defects in hijab print productis is still high. The defects found were clumping ink, blotches, stripe motifs, and torn threads. It causes low quality products. This study aimed to reduce the number of product defects in hijab print production. This study included quantitative research and used primary and secondary data sources while implementing six sigma with the DMAIC method. Based on data analysis, it was found that the most influential factor for the product defects was the overworked heat press machine. Improvements were made by setting the most optimal machine input temperature and stop instructions for machine to cooling down. These improvements were then standardized into standard procedures in the form of work instructions and check sheets. The results indicated that the DPMO value decreased from 29,308 to 14,000, increasing the sigma value from 3.37 to 3.77. In conclusion, the implementation of six sigma using the DMAIC method was able to reduce the number of product defects while increasing the sigma value, increasing product